Analisis Pengaruh Pricing, Kepercayaan, Dan Pelayanan Terhadap Keputusan Nasabah Pembiayaan Mikro Produk Murabahah (Study Kasus BSI Simpang Mulieng) - Nursafitri, Yessi; Hafizh, Muhammad (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2024)
This research aims to determine the analysis of the influence of pricing, trust and service on customers' decisions to finance micro murabahah products (case study of BSI Simpang Mulieng). This researcher took a sample of 38 data from customers responding to micro murabahah financing products at BSI Simpang Mulieng in 2021-2023, which was collected using a total sampling technique and the data was measured using a Likert scale and processed with the help of SPSS 26. From the results of the research on the T test, pricing was obtained. (X1) has a positive effect on customer decisions (Y) regarding financing micro murabahah products at Bsi Simpang Mulieng. seen from the tcount value of 2.704 > ttable 2.032 and the significance value of 0.009 < 0.01. Trust (X2) has a positive effect on customer decisions (Y) on murabahah financing at Bsi Simpang Mulieng, seen from the t-count value of 2.222 > 2.032 and a significant value of 0.033 < 0.1. Service micro murabahah product financing at BSI Simpang Mulieng. Judging from the calculated f value > f table with a value of 38.975 > 2.88 with a significance value of 0.000 < 0.05. And the results of the coefficient of determination test (R2) show that the three independent variables (X1. margin and service quality and the remaining 24.5% are influenced by other variables not included in the research.